Low-water-absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering and preparation method of low-water-absorption carbon fiber reinforced nylon 6 powder material
By modifying nylon 6 resin and adding carbon fiber micro powder, the mechanical performance degradation caused by the high water absorption rate of nylon 6 materials is solved, and materials with low water absorption rate and high mechanical properties are achieved, which are suitable for aerospace and other fields.
Patent Information
- Application Number
- CN202411499117.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-07
AI Technical Summary
The high water absorption rate of nylon 6 material leads to its mechanical properties degradation and dimensional instability, limiting its application in aerospace, chemical and other fields.
By modifying the nylon 6 resin, the complexation reaction is carried out with metal ions (such as calcium chloride) and the amide groups on the nylon 6 molecular chain to reduce the formation of hydrogen bonds, thereby reducing the water absorption rate, and adding carbon fiber micro powder to improve mechanical properties.
The nylon 6 powder material with low water absorption and high mechanical properties has been achieved, and the water absorption rate is reduced to below 0.8%, and the tensile strength reaches 115MPa, which significantly improves the stability of the material and the high-temperature and low-temperature environmental performance.
Smart Images

Figure CN119570079A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additive manufacturing, and specifically relates to a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering and a preparation method thereof. Background Art
[0002] Nylon 6 is a polymer compound, also known as PA6, polyamide and nylon 6; it has the characteristics of high strength, high heat resistance, wear resistance, chemical corrosion resistance and excellent comprehensive performance. Therefore, it is widely used in aerospace, chemical, automotive and other fields. Because nylon 6 contains a large number of hydrophilic amide groups (-NHCO-) in its molecular chain, its high water absorption property has always been an important factor affecting the application of materials. After absorbing water, the mechanical properties of nylon 6 materials decrease, such as hardness, modulus, tensile strength and product dimensional stability. The long-term performance of the material is affected by the change in material size, which greatly restricts the use of nylon 6 materials.
[0003] Laser 3D printing technology is an emerging technology in the field of rapid prototyping. It is based on digital model files and uses powdered metal or plastic and other bondable materials. Powder materials used at the industrial level include metal powder, nylon 12 powder and nylon 11 powder. These powder materials are expensive and costly to use, which greatly limits their industrial applications. With the continuous development of products and the gradual implementation of new standards, nylon 6 material, as a widely used plastic, has low price and excellent mechanical properties and has been widely used in traditional industries.
[0004] However, the water absorption problem of nylon 6 material seriously affects the use restrictions of the material. The existing technology improves the water resistance of nylon 6 products by adding fillers, but too much filler often causes a significant decrease in the mechanical properties of the material. Carbon fiber can be added to the resin as a reinforcing material to form a composite material, which significantly increases the mechanical properties and rigidity of the material. Therefore, nylon 6 with low water absorption and high mechanical properties is an important direction of current SLS application material research. Summary of the invention
[0005] The present invention provides a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering and a preparation method thereof, which is used to solve the problem of high water absorption of nylon 6. At the same time, the nylon 6 powder material prepared by the present invention has excellent mechanical properties.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering, characterized in that it comprises the following steps:
[0008] (1) adding nylon 6 resin, calcium chloride, antioxidant and lubricant into a high-speed mixer and mixing them evenly, and then extruding and granulating them through a twin-screw extruder to obtain a nylon 6 masterbatch with low water absorption;
[0009] (2) adding low water absorption nylon 6 masterbatch and mixed solvent into a reaction kettle, stirring and heating, and keeping the temperature when the material is heated to the crystallization temperature of low water absorption nylon 6;
[0010] (3) After the insulation is completed, the material in the reactor is cooled to precipitate nylon 6 powder particles with low water absorption rate;
[0011] (4) subjecting the low water absorption nylon 6 powder particles to liquid phase separation, drying and classification to obtain low water absorption nylon 6 powder;
[0012] (5) Adding low water absorption nylon 6 powder, carbon fiber powder and flow aid into a high-speed mixer and uniformly stirring, a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering is obtained.
[0013] Preferably, the mass of the calcium chloride is 5-10% of the mass of the nylon 6 resin, the mass of the antioxidant is 0.1%-0.5% of the mass of the nylon 6 resin, and the mass of the lubricant is 0.1-0.5% of the mass of the nylon 6 resin.
[0014] Preferably, the mass of the carbon fiber powder is 10-30% of the sum of the mass of the low water absorption nylon 6 powder and the carbon fiber powder, and the mass of the flow aid is 0.1-0.3% of the sum of the mass of the low water absorption nylon 6 powder and the carbon fiber powder.
[0015] Preferably, the nylon 6 resin has a viscosity ranging from 2 to 2.8 mPa.
[0016] Preferably, the calcium chloride is nano anhydrous calcium chloride.
[0017] Preferably, in step (1), the rotation speed of the high-speed mixer is 200-400 r / min, and the mixing time is 5-8 min.
[0018] Preferably, the screw length-to-diameter ratio of the twin-screw extruder is 30:1-52:1, the screw speed is 500-1000 r / min, and the temperature of each section of the twin-screw extruder is 190-270°C.
[0019] Preferably, the mass ratio of the low water absorption nylon 6 masterbatch to the mixed solvent is 1:5 to 1:10; the mixed solvent is a mixture of water and other solvents, wherein the mass ratio of water to other solvents is 1:1, the other solvents are one or more of methanol, ethanol, dimethylformamide, and dimethyl sulfoxide, and the water is one or more of purified water, deionized water, and industrial water.
[0020] Preferably, in step (2), the stirring rate is 200-300 r / min, the heating temperature is 140-160° C., the insulation time is 1-3 h, and the pressure in the reactor is maintained at 0.7-1.2 MPa.
[0021] Preferably, in step (3), the temperature is first slowly lowered to 90-100° C. at a rate of 0.2-0.5° C. / min, and then lowered to room temperature at a rate of 5-10° C. / min to precipitate nylon 6 powder particles with low water absorption.
[0022] Preferably, in step (4), the low water absorption nylon 6 powder particles are dried in an oven at 80-100° C. for 8-12 hours and are graded using a sieve of 80-120 mesh.
[0023] Preferably, in step (5), the stirring time is 5 to 8 minutes, and the stirring speed is 160 to 200 r / min; after uniform stirring in a high-speed stirrer, the mixture is sieved with an 80 to 120 mesh sieve to obtain a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering with an average particle size of 50 to 120 um.
[0024] Preferably, the carbon fiber powder has a diameter of 8 to 10 um and a length of 40 to 100 um.
[0025] Preferably, the flow aid is one or more of fumed silica, fumed alumina, nano-titanium dioxide, and nano-silicon dioxide.
[0026] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 1098, antioxidant 168, and antioxidant S-9228.
[0027] Preferably, the lubricant is one or more of calcium stearate, silicone powder, white oil, organosilicon compound, stearate, and polyethylene wax.
[0028] A low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering is prepared by adopting the preparation method of the low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering.
[0029] The beneficial effects of the present invention are as follows:
[0030] 1. The low water absorption carbon fiber reinforced nylon 6 powder material provided by the present invention is obtained by modifying nylon 6 resin and using metal ions to carry out complexation reaction on the molecular chain of nylon 6 resin to reduce the number of hydrogen bonds formed on its molecular chain, so that its molecules have ultra-low water absorption; at the same time, the addition of carbon fiber can further reduce the water absorption of nylon 6 powder material, and at the same time effectively improve the mechanical properties, stability and high temperature and low temperature environment resistance of the material, which can meet the market demand for water absorption and mechanical ability of nylon materials and has good application prospects.
[0031] 2. The process of the present invention is simple to operate. In the process of powder making, the mixed solvent can be reused, and the addition of water solvent can reduce the production cost. By controlling the cooling rate, the size and morphology of the powder particles can be improved. The average particle size of the prepared powder is 50 to 120 um, and the powder has good fluidity, which is conducive to SLS processing.
[0032] 3. The low water absorption carbon fiber reinforced nylon 6 powder prepared by the present invention has excellent mechanical properties in the selective laser sintering application, and its tensile strength is twice as high as that of the current PA12 and PA11 materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the complexation reaction between the amide group in nylon 6 and CaCl3;
[0034] Figure 2 This is a morphology comparison diagram of the material prepared in Comparative Example 3 under a 160x microscope;
[0035] Figure 3 This is a comparison of the morphologies of the materials prepared in Example 1 under a microscope at 800 times magnification. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below in conjunction with the embodiments.
[0037] The water absorption test method of low water absorption nylon 6 composite material is as follows: the SLS sintered specimen is placed in a vacuum oven at 80℃ for 24 hours and then cooled to room temperature in the oven. The specimen is taken out and weighed under constant temperature and humidity at 25℃ to obtain the mass m0; the specimen is then placed in a deionized water bath at room temperature of 25℃ and soaked for 24 hours. The specimen is taken out and wiped dry with a dry cloth and quickly weighed to obtain the mass m1 and the water absorption W. f It can be obtained from the equation:
[0038]
[0039] Comparative Example 1
[0040] (1) Add 5 kg of nylon 6 resin, 0.025 kg of antioxidant 1010 and 30 kg of mixed solvent (15 kg of methanol and 15 kg of deionized water) into a reactor. After nitrogen is filled into the reactor and vented, seal the reactor and stir and heat at a stirring rate of 220 r / min. When the temperature in the reactor rises to 160°C and the pressure in the reactor is 0.9 MPa, stir and heat for 1 hour.
[0041] (2) After the insulation is completed, the temperature of the materials in the reactor is cooled, first slowly cooled to 90°C at a rate of 0.2°C / min, and then quickly cooled to room temperature at a rate of 5°C / min, to precipitate nylon 6 powder particles.
[0042] (3) The nylon 6 powder particles were subjected to liquid phase separation and oven drying at a drying temperature of 95° C. for a drying time of 10 h, and then sieved and graded with a 100-mesh sieve to obtain nylon 6 powder with an average particle size of 65 μm.
[0043] (4) 4 kg of nylon 6 powder and 0.012 kg of fumed silica were added to a high-speed mixer and stirred evenly at a stirring rate of 160 r / min for 8 min. The powder was then sieved with a 90-mesh sieve to obtain nylon 6 powder with an average particle size of 67 μm for selective laser sintering.
[0044] The above nylon 6 powder was molded on the SLS equipment, and the preparation process parameters were: laser power 45W, scanning speed 4000mm / s, scanning spacing 0.25, sintering layer thickness 0.1mm; the SLS prepared specimens were obtained for mechanical properties and water absorption test, and the results are shown in Table 1.
[0045] Comparative Example 2
[0046] (1) 5 kg of nylon 6 resin, 0.5 kg of nano anhydrous calcium chloride, 0.012 kg of antioxidant 168, and 0.025 kg of calcium stearate were added to a high-speed mixer and mixed evenly at a speed of 200 r / min for a mixing time of 8 min; then, the mixture was extruded and granulated by a twin-screw extruder. The temperatures of each section of the twin-screw extruder were: 190° C. for zone 1, 215° C. for zone 2, 235° C. for zone 3, 245° C. for zone 4, 255° C. for zone 5, 265° C. for zone 6, 270° C. for die head, and a screw speed of 1000 r / min to obtain a nylon 6 masterbatch with low water absorption.
[0047] (2) Add low water absorption nylon 6 masterbatch and 50 kg of mixed solvent (25 kg of ethanol and 25 kg of pure water) into the reactor, fill the reactor with nitrogen and exhaust it, then seal the reactor, stir and heat it at a stirring rate of 265 r / min. When the temperature in the reactor rises to 155°C and the pressure in the reactor is 1.1 MPa, keep it warm and stir for 2 hours.
[0048] (3) After the insulation is completed, the temperature of the materials in the reactor is cooled, first slowly cooled to 90°C at a rate of 0.5°C / min, and then quickly cooled to room temperature at a rate of 8°C / min, to precipitate low water absorption nylon 6 powder particles.
[0049] (4) The low water absorption nylon 6 powder particles were subjected to liquid phase separation and oven drying at a drying temperature of 100° C. for a drying time of 8 h, and then sieved and graded with a 100-mesh sieve to obtain a low water absorption nylon 6 powder with an average particle size of 59 μm.
[0050] (5) 4 kg of low water absorption nylon 6 powder and 0.012 kg of fumed silica were added to a high-speed mixer and stirred evenly at a stirring rate of 180 r / min for 6 min. The mixture was then sieved with a 100-mesh sieve to obtain a low water absorption nylon 6 powder with an average particle size of 57 μm for selective laser sintering.
[0051] The above-mentioned low water absorption nylon 6 powder was molded on the SLS equipment, and the preparation process parameters were: laser power 50W, scanning speed 4000mm / s, scanning spacing 0.3, sintering layer thickness 0.1mm; the SLS prepared specimens were obtained for mechanical properties and water absorption tests, and the results are shown in Table 1.
[0052] Comparative Example 3
[0053] (1) Add 5 kg of nylon 6 resin, 0.005 kg of antioxidant 1098 and 40 kg of mixed solvent (20 kg of methanol and 20 kg of deionized water) into a reactor. After nitrogen is filled and exhausted in the reactor, the reactor is sealed and stirred and heated at a stirring rate of 240 r / min. When the temperature in the reactor rises to 160°C and the pressure in the reactor is 1.2 MPa, stir and heat for 1.5 hours.
[0054] (2) After the insulation is completed, the temperature of the materials in the reactor is cooled, first slowly cooled to 95°C at a rate of 0.4°C / min, and then quickly cooled to room temperature at a rate of 10°C / min, to precipitate nylon 6 powder particles.
[0055] (3) The nylon 6 powder particles were separated by a liquid box and dried in an oven at a drying temperature of 80° C. for a drying time of 10 h. The nylon 6 powder particles were then sieved and graded with a 120-mesh sieve to obtain a nylon 6 powder with an average particle size of 73 μm.
[0056] (4) 3.6 kg of nylon 6 powder, 0.4 kg of carbon fiber powder and 0.008 kg of fumed silica were added to a high-speed mixer and stirred evenly at a stirring rate of 200 r / min for 5 min. The powder was then sieved with a 100-mesh sieve to obtain a carbon fiber reinforced nylon 6 powder with an average particle size of 76 μm for selective laser sintering. Figure 2 shown.
[0057] The above carbon fiber reinforced nylon 6 powder was molded on the SLS equipment, and the preparation process parameters were: laser power 50W, scanning speed 4000mm / s, scanning spacing 0.3, sintering layer thickness 0.1mm; the SLS prepared specimens were obtained for mechanical properties and water absorption test, and the results are shown in Table 1.
[0058] Example 1
[0059] (1) 5 kg of nylon 6 resin, 0.25 kg of nano anhydrous calcium chloride, 0.012 kg of antioxidant 1010, and 0.025 kg of calcium stearate were added to a high-speed mixer and mixed evenly at a speed of 400 r / min for a mixing time of 5 min; then, the mixture was extruded and granulated by a twin-screw extruder. The temperatures of each section of the twin-screw extruder were: 200° C. for zone 1, 215° C. for zone 2, 225° C. for zone 3, 235° C. for zone 4, 245° C. for zone 5, 265° C. for zone 6, 265° C. for die head, and 800 r / min for screw speed, to obtain a nylon 6 masterbatch with low water absorption rate, see Figure 1 shown.
[0060] (2) Add low water absorption nylon 6 masterbatch and 50 kg of mixed solvent (25 kg of ethanol and 25 kg of pure water) into the reactor, fill the reactor with nitrogen and exhaust it, then seal the reactor, stir and heat it at a stirring rate of 270 r / min. When the temperature in the reactor rises to 150°C and the pressure in the reactor is 1.0 MPa, keep it warm and stir for 3 hours.
[0061] (3) After the insulation is completed, the temperature of the materials in the reactor is cooled, first slowly cooled to 90°C at a rate of 0.5°C / min, and then quickly cooled to room temperature at a rate of 8°C / min, to precipitate low water absorption nylon 6 powder particles.
[0062] (4) The low water absorption nylon 6 powder particles were separated by a liquid box and dried in an oven at a drying temperature of 100° C. for 8 h. The particles were then sieved and graded with a 100-mesh sieve to obtain a low water absorption nylon 6 powder with an average particle size of 53 μm.
[0063] (5) 3.6 kg of low water absorption nylon 6 powder, 0.4 kg of carbon fiber powder and 0.004 kg of fumed silica were added to a high-speed mixer and stirred evenly at a stirring rate of 160 r / min for 8 min. The mixture was then sieved with an 80-mesh sieve to obtain a low water absorption carbon fiber reinforced nylon 6 powder material with an average particle size of 59 μm for selective laser sintering. Figure 3 shown.
[0064] The above-mentioned low water absorption carbon fiber reinforced nylon 6 powder material was molded on the SLS equipment, and the preparation process parameters were: laser power 45W, scanning speed 3800mm / s, scanning spacing 0.25, sintering layer thickness 0.1mm; the SLS prepared specimens were obtained for mechanical properties and water absorption tests, and the results are shown in Table 1.
[0065] Example 2
[0066] (1) 5 kg of nylon 6 resin, 0.5 kg of nano anhydrous calcium chloride, 0.01 kg of antioxidant 168 and 0.025 kg of white oil were added to a high-speed mixer and mixed evenly at a speed of 250 r / min for a mixing time of 6 min; then, the mixture was extruded and granulated by a twin-screw extruder. The temperatures of each section of the twin-screw extruder were as follows: 190° C. for zone 1, 205° C. for zone 2, 235° C. for zone 3, 245° C. for zone 4, 265° C. for zone 5, 270° C. for zone 6, 270° C. for die head, and 800 r / min for screw speed, to obtain a nylon 6 masterbatch with low water absorption.
[0067] (2) Add low water absorption nylon 6 masterbatch and 46 kg of mixed solvent (23 kg of ethanol and 23 kg of pure water) into the reactor, fill the reactor with nitrogen and exhaust it, then seal the reactor, stir and heat it at a stirring rate of 280 r / min. When the temperature in the reactor rises to 140°C and the pressure in the reactor is 0.7 MPa, keep it warm and stir for 3 hours.
[0068] (3) After the insulation is completed, the temperature of the materials in the reactor is cooled, first slowly cooled to 100°C at a rate of 0.2°C / min, and then quickly cooled to room temperature at a rate of 5°C / min, to precipitate low water absorption nylon 6 powder particles.
[0069] (4) The low water absorption nylon 6 powder particles were subjected to liquid phase separation and oven drying at a drying temperature of 80° C. for a drying time of 10 h, and then sieved and graded with a 100-mesh sieve to obtain a low water absorption nylon 6 powder with an average particle size of 73 μm.
[0070] (5) 3.2 kg of low water absorption nylon 6 powder, 0.8 kg of carbon fiber powder and 0.012 kg of fumed silica were added to a high-speed mixer and stirred evenly at a stirring rate of 200 r / min for 5 min. The mixture was then sieved with an 80-mesh sieve to obtain a low water absorption carbon fiber reinforced nylon 6 powder material with an average particle size of 76 μm for selective laser sintering.
[0071] The above-mentioned low water absorption carbon fiber reinforced nylon 6 powder was molded on the SLS equipment, and the preparation process parameters were: laser power 45W, scanning speed 3800mm / s, scanning spacing 0.25, sintering layer thickness 0.1mm; the SLS prepared specimens were obtained for mechanical properties and water absorption tests, and the results are shown in Table 1.
[0072] Example 3
[0073] (1) 5 kg of nylon 6 resin, 0.25 kg of nano anhydrous calcium chloride, 0.01 kg of antioxidant 168, and 0.005 kg of white oil were added to a high-speed mixer and mixed evenly at a speed of 200 r / min for a mixing time of 8 min; then, the mixture was extruded and granulated by a twin-screw extruder. The temperatures of each section of the twin-screw extruder were: 215° C. for zone 1, 235° C. for zone 2, 245° C. for zone 3, 255° C. for zone 4, 265° C. for zone 5, 265° C. for zone 6, 265° C. for die head, and a screw speed of 800 r / min to obtain a nylon 6 masterbatch with low water absorption.
[0074] (2) Add low water absorption nylon 6 masterbatch and 30 kg of mixed solvent (15 kg of ethanol and 15 kg of deionized water) into the reactor, fill the reactor with nitrogen and exhaust it, then seal the reactor, stir and heat it at a stirring rate of 285 r / min. When the temperature in the reactor rises to 145°C and the pressure in the reactor is 0.8 MPa, keep it warm and stir for 2 hours.
[0075] (3) After the insulation is completed, the temperature of the materials in the reactor is cooled, first slowly cooled to 95°C at a rate of 0.3°C / min, and then quickly cooled to room temperature at a rate of 5°C / min, to precipitate nylon 6 powder particles with low water absorption.
[0076] (4) The low water absorption nylon 6 powder particles were subjected to liquid phase separation and oven drying at a drying temperature of 80° C. for a drying time of 10 h, and then sieved and graded with a 100-mesh sieve to obtain a low water absorption nylon 6 powder with an average particle size of 66 μm.
[0077] (5) 2.8 kg of low water absorption nylon 6 powder, 1.2 kg of carbon fiber powder and 0.008 kg of fumed silica were added to a high-speed mixer and uniformly stirred at a stirring rate of 200 r / min for 5 min. The mixture was then sieved with an 80-mesh sieve to obtain a low water absorption carbon fiber reinforced nylon 6 powder material with an average particle size of 69 um for selective laser sintering.
[0078] The above-mentioned low water absorption carbon fiber reinforced nylon 6 powder was molded on the SLS equipment, and the preparation process parameters were: laser power 45W, scanning speed 3800mm / s, scanning spacing 0.25, sintering layer thickness 0.1mm; the SLS prepared specimens were obtained for mechanical properties and water absorption tests, and the results are shown in Table 1.
[0079]
[0080] Table 1: Water absorption and mechanical properties test results of SLS prepared specimens
[0081] It can be seen from the experimental data in Table 1 that the water absorption rate of the nylon powder in Comparative Example 2 is 1.7%, which is about one-half of the water absorption rate of Comparative Example 1. This shows that when the nanometer anhydrous calcium chloride particles are added to the nylon 6 resin molecular chain, the calcium ions can react with the amide groups of nylon 6 to reduce the number of hydrogen bonds formed in the nylon 6 molecular chain, greatly reducing the water absorption rate of the nylon 6 material. The experimental data of Comparative Example 3 show that the addition of carbon fiber can also reduce the water absorption rate of nylon 6 material, but it is not as obvious as the effect of nanometer anhydrous calcium chloride particles; the mechanical properties of nylon 6 composite materials are not well improved. The water absorption rate of the low water absorption carbon fiber reinforced nylon 6 composite powder material prepared by implementing 1 to 3 is below 0.8%, which is much lower than 3.2% of Comparative Example 1. Its tensile strength in the XY direction can reach 115MPa. The addition of carbon fiber can effectively improve the tensile strength and elastic modulus of nylon 6 powder material, especially the tensile strength in the Z direction. The toughness and strength of low water absorption carbon fiber reinforced nylon 6 powder materials are improved at the same time. The low water absorption ensures the dimensional stability of the material, further expanding the application areas and usage scenarios of nylon 6 resin.
[0082] The above description of the disclosed embodiments is intended only to enable those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the implementations shown herein but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering, characterized in that: The steps include: (1) adding nylon 6 resin, calcium chloride, antioxidant and lubricant into a high-speed mixer and mixing them evenly, and then extruding and granulating them through a twin-screw extruder to obtain a nylon 6 masterbatch with low water absorption; (2) adding low water absorption nylon 6 masterbatch and mixed solvent into a reaction kettle, stirring and heating, and keeping the temperature when the material is heated to the crystallization temperature of low water absorption nylon 6; (3) After the insulation is completed, the material in the reactor is cooled to precipitate nylon 6 powder particles with low water absorption rate; (4) subjecting the low water absorption nylon 6 powder particles to liquid phase separation, drying and classification to obtain low water absorption nylon 6 powder; (5) Adding low water absorption nylon 6 powder, carbon fiber powder and flow aid into a high-speed mixer and uniformly stirring, a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering is obtained.
2. The method for preparing the low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: The mass of the calcium chloride is 5-10% of the mass of the nylon 6 resin, the mass of the antioxidant is 0.1%-0.5% of the mass of the nylon 6 resin, and the mass of the lubricant is 0.1%-0.5% of the mass of the nylon 6 resin; The mass of the carbon fiber powder is 10-30% of the sum of the mass of the low water absorption nylon 6 powder and the carbon fiber powder, and the mass of the flow aid is 0.1-0.3% of the sum of the mass of the low water absorption nylon 6 powder and the carbon fiber powder; The viscosity of the nylon 6 resin is in the range of 2 to 2.8 mPa; and the calcium chloride is nano anhydrous calcium chloride.
3. The method for preparing the low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: In step (1), the speed of the high-speed mixer is 200-400 r / min, and the mixing time is 5-8 min; The screw length-diameter ratio of the twin-screw extruder is 30:1-52:1, the screw speed is 500-1000 r / min, and the temperature of each section of the twin-screw extruder is 190-270°C.
4. The method for preparing the low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: The mass ratio of the low water absorption nylon 6 masterbatch to the mixed solvent is 1:5 to 1:10; The mixed solvent is a mixture of water and other solvents, wherein the mass ratio of water to other solvents is 1:1, the other solvents are one or more of methanol, ethanol, dimethylformamide, and dimethyl sulfoxide, and the water is one or more of purified water, deionized water, and industrial water.
5. The method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: In step (2), the stirring rate is 200-300 r / min, the heating temperature is 140-160° C., the insulation time is 1-3 h, and the pressure in the reactor is maintained at 0.7-1.2 MPa.
6. The method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: In step (3), the temperature is firstly lowered to 90-100°C at a rate of 0.2-0.5°C / min, and then lowered to room temperature at a rate of 5-10°C / min to precipitate nylon 6 powder particles with low water absorption.
7. The method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: In step (4), the low water absorption nylon 6 powder particles are dried in an oven at 80 to 100° C. for 8 to 12 hours and are classified using a sieve of 80 to 120 meshes.
8. The method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: In step (5), the stirring time is 5 to 8 minutes, and the stirring speed is 160 to 200 r / min; after being uniformly stirred by a high-speed stirrer, the mixture is sieved with a 80 to 120 mesh sieve to obtain a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering with an average particle size of 50 to 120 μm.
9. The method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: The diameter of the carbon fiber powder is 8-10um, and the length is 40-100um; the flow aid is one or more of fumed silicon dioxide, fumed aluminum oxide, nano titanium dioxide, and nano silicon dioxide.
10. The method for preparing a low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1098, antioxidant 168, and antioxidant S-9228; The lubricant is one or more of calcium stearate, silicone powder, white oil, organic silicon compound, stearate, and polyethylene wax.
11. A low water absorption carbon fiber reinforced nylon 6 powder material for selective laser sintering, characterized in that: The powder material is prepared by the method for preparing a carbon fiber reinforced nylon 6 powder material with low water absorption for selective laser sintering according to any one of claims 1 to 10.